2020
DOI: 10.3390/su12124878
|View full text |Cite
|
Sign up to set email alerts
|

Could MOOC-Takers’ Behavior Discuss the Meaning of Success-Dropout Rate? Players, Auditors, and Spectators in a Geographical Analysis Course about Natural Risks

Abstract: Research interest in massive online and open courses (MOOCs) is rapidly growing, questioning who enrolls, why and how to conceive engagement, and success rates. This study is focused on MOOC-takers behavior obtained from a seven-week MOOC experience on natural risks. Data scraping principles have been used to collect data. Demographics, success-dropout rates, engagement periods, achievement and scoring, and behavior were analyzed through descriptive statistics, non-parametric correlation analysis, and statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 71 publications
1
17
0
Order By: Relevance
“…Our empirical results proved that students' outcomes during the online learning process are affected by 6 factors in the descending order, respectively, learner characteristics, perceived usefulness, course content, course design, ease of use, and faculty capacity (see Table 7). is result is also similar to that of studies in [2,13,14,28,31].…”
Section: Conclusion and Policy Implicationssupporting
confidence: 91%
See 1 more Smart Citation
“…Our empirical results proved that students' outcomes during the online learning process are affected by 6 factors in the descending order, respectively, learner characteristics, perceived usefulness, course content, course design, ease of use, and faculty capacity (see Table 7). is result is also similar to that of studies in [2,13,14,28,31].…”
Section: Conclusion and Policy Implicationssupporting
confidence: 91%
“…A good course design will attract and facilitate students to learn through online classes [25]. e course design interface is used to introduce course content, designed according to student's competence and level of understanding, and appropriate in terms of time and space to promote and support the self-study process [26][27][28]. Based on these rationales, the following hypothesis is designed for this study.…”
Section: Coursementioning
confidence: 99%
“…A study by Ashwin and McVitty (2015) also found that interactive course content and a dynamic and flexible technology-mediated teaching and learning environment have a significant influence on the behavioural intentions of lecturers to teach online. Separate studies by Oh et al (2020), Ahmad et al (2018) and Ricart et al (2020) further found that ICT-mediated teaching that is highly interactive and that is in line with students' learning needs, interest and styles significantly contributed to the behavioural intentions of university lecturers to teach online. A study by Uslu et al (2018) found that lecturers with an orientation for teacher-centred tend to use instructor-and skill-oriented software during online teaching, while lecturers with a student-centred teaching orientation tend to use openended software to ensure active participation, productive skills and the structuring of learning.…”
Section: Pedagogical Factorsmentioning
confidence: 97%
“…Similarly, Zhou (2016) argued that students' attitude towards MOOCs significantly impacts using MOOCs. Recently, Ricart et al (2020) explored that MOOC-takers' engagement, academic performance and the completion–dropout rate are significantly influenced by their attitude.…”
Section: Review Of the Literaturementioning
confidence: 99%